2011
DOI: 10.1099/ijs.0.026484-0
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium vallis sp. nov., isolated from nodules of three leguminous species

Abstract: Four bacterial strains isolated from root nodules of Phaseolus vulgaris, Mimosa pudica and Indigofera spicata plants grown in the Yunnan province of China were identified as a lineage within the genus Rhizobium according to the analysis of 16S rRNA gene sequences, sharing most similarity with Rhizobium lusitanum P1-7 T (99.1 % sequence similarity) and Rhizobium rhizogenes IAM 13570 T (99.0 %). These strains also formed a distinctive group from the reference strains for defined species of the genus Rhizobium in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 48 publications
1
14
0
1
Order By: Relevance
“…The present study has confirmed that Cupriavidus strains similar to C. taiwanensis are common symbionts of M. pudica in several other locations in India, but has gone further and shown for the first time that strains in the species B. mimosarum and B. phymatum are also common M. pudica symbionts, and even that some Rhizobium strains (e.g. MP10, which is similar to R. vallis; Wang et al, 2011) can be symbiotic with this species in India. Our study of M. pudica symbionts in India has some parallels with that of Liu et al (2012) from southern China, in which the same three species, C. taiwanensis, B. mimosarum and B. phymatum, were always found to nodulate M. pudica in varying proportions depending upon location, but the present study differs from Liu et al (2012) in that some sites in India were dominated by one symbiont type, e.g.…”
Section: Molecular Characterization Of Symbionts Of Native and Invasisupporting
confidence: 76%
“…The present study has confirmed that Cupriavidus strains similar to C. taiwanensis are common symbionts of M. pudica in several other locations in India, but has gone further and shown for the first time that strains in the species B. mimosarum and B. phymatum are also common M. pudica symbionts, and even that some Rhizobium strains (e.g. MP10, which is similar to R. vallis; Wang et al, 2011) can be symbiotic with this species in India. Our study of M. pudica symbionts in India has some parallels with that of Liu et al (2012) from southern China, in which the same three species, C. taiwanensis, B. mimosarum and B. phymatum, were always found to nodulate M. pudica in varying proportions depending upon location, but the present study differs from Liu et al (2012) in that some sites in India were dominated by one symbiont type, e.g.…”
Section: Molecular Characterization Of Symbionts Of Native and Invasisupporting
confidence: 76%
“…Strains belonging to several species of the rhizobia genera have previously been isolated from the root nodules of leguminous plants (Zhang et al 1991;Wang et al 2010). However, a large number of native microbial population studies also include rhizobia species in the bulk soil and rhizosphere of non-leguminous plants Arruda et al 2012;Farina et al 2012;Souza et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that these fields may be good candidates to establish novel populations of effective rhizobia with less competitive interference from indigenous strains. While many species of rhizobia can nodulate dry beans (Martinez-Romero et al, 1991;Segovia et al, 1993;Wang et al, 2011), this study found only two main species of dry bean-rhizobia in organic fields; R. leguminosarum bv. phaseoli (67.1%) and R. etli (30.2%).…”
Section: Discussionmentioning
confidence: 54%